2015
DOI: 10.1039/c4cy01547a
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for intensification of Fischer–Tropsch synthesis through reduced formation of methane over cobalt catalysts in microreactors

Abstract: In this review we discuss the reasons responsible for higher than expected methane selectivity during Fischer–Tropsch synthesis (FTS) over cobalt-based catalysts and describe novel microreactors for use in FTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 108 publications
0
24
0
Order By: Relevance
“…However, considering that the vast majority of modern chemical processes utilise heterogeneous catalysts to replace stoichiometric reactions due to obvious economic and environmental advantages, the application of catalytic coatings in microreactors is disproportionately scarcely studied [17]. A few gas-phase heterogeneously catalysed reactions have been studied in various reactions such as Fisher-Tropsch synthesis, CO2 hydrogenation, water gas shift [18], preferential CO oxidation [19], and complete oxidation of organic compounds [20] demonstrating a 2-5 fold increase in reaction rates compared to conventional reactors [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that the vast majority of modern chemical processes utilise heterogeneous catalysts to replace stoichiometric reactions due to obvious economic and environmental advantages, the application of catalytic coatings in microreactors is disproportionately scarcely studied [17]. A few gas-phase heterogeneously catalysed reactions have been studied in various reactions such as Fisher-Tropsch synthesis, CO2 hydrogenation, water gas shift [18], preferential CO oxidation [19], and complete oxidation of organic compounds [20] demonstrating a 2-5 fold increase in reaction rates compared to conventional reactors [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Schematic showing the GTL process involving FT 18 2.2 Biomass-to-liquid (BTL) Biomass can typically be categorised into three main categories: (i) vegetable oils such as palm and soybean oil, (ii) carbohydrates for example, starch and sugars and (iii) lignocellulose solid materials derived from wood 15 . Biofuels produced from these feedstocks can be classified into first, second and third generation biofuels.…”
Section: Figurementioning
confidence: 99%
“…Although using a packed bed microreactor has several benefits, these particular reactors are often subject to high pressure drops due to the use of small catalyst pellets. However, it was found that an adequate level of pressure drop can be achieved with substantially small catalyst pellets (100 µm) while retaining a high catalyst effectivity 18 . Using packed bed microreactors has proven to be beneficial for liquid fuel synthesis but they can be subject to plugging or fowling of the channel network due to the use of solid catalyst particles.…”
Section: Packed Bed Microreactorsmentioning
confidence: 99%
See 2 more Smart Citations